Closed Loop Non Linear Control of Shunt Hybrid Power Filter for Harmonics Mitigation in Industrial Distribution System - Arivarasu A; Muthukumar K; Balasubramanian R (Institute of Advanced Engineering and Science, 2014)
In recent years, the amount of non-linear loads has been increasing considerably since there are improvements in power electronic equipment (such as adjustable speed drives or converter ac-dc, ac-ac, dc-ac and dc-dc) in industrial sectors which cause deterioration of the quality of the electric power supply through distortion of supply voltage and supply current. This has led to improvement of many stringent needs regarding generation of harmonic current, which are found in IEEE519 and IEC61000 standards. This paper proposes a non-linear function based closed loop control strategy (without load current extraction) for three-phase Shunt Active Power Line Conditioner and LC passive filter to compensate harmonics, power factor improvement and enhance the dynamic performance of Shunt Hybrid Power Filter (SHPF). By using a PI controller the DC bus voltage of the Shunt Active Power Filter is maintained constant. Results obtained from simulation shows the performance of expected hybrid filter in transient and steady state operation .This indicates that the controller is able to compensate even under severe load current imbalances.DOI: http://dx.doi.org/10.11591/ijpeds.v5i2.6181